Comparative Study of Superior Potential of ComSTUDI KOMPARATIF POTENSI UNGGULAN HUTAN RAKYAT UNTUK PRIORITAS PENGEMBANGAN DI PROVINSI JAWA TENGAH munity Forest for Priority Development in Central Java Province - Suhartono, Suhartono (Jurnal AGRISEP, 2019)
Deforestation rates of forest areas due to over functions of the area are one of the causes of declining production of natural forest timber. The Government of Indonesia via Ministry of Environment and Forestry made the solution to meet the needs of timberwith the development of centers of wood production from private forests. This study aims to identify potential areas of community forests that have comparative advantages for development priorities in Central Java. The data used is the growth of private forest area in Central Java Province during 2011-2015. Data analysis using Location Quotient (LQ) and Specialization Quotient(SQ) method. The result of the research showed thatthe community forest sector in Central Java is not a specialized sector.There are 18 regencies/cities as potential forest area are Purbalingga District, Kendal District, Salatiga City, Purworejo District, Banjarnegara District, Sukoharjo District, Cilacap District, Sragen District, Pekalongan District, Wonogiri District, Temanggung District, Magelang District, Wonosobo District, Karanganyar District, Boyolali District, Batang District, Banyumas District and Pati District with total area of 456,575.85 Ha which can be a priority in developing communityforest in Central Java.